2015
DOI: 10.1101/cshperspect.a023473
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Preeclampsia

Abstract: Preeclampsia is a pregnancy-specific disease characterized by new onset hypertension and proteinuria after 20 wk of gestation. It is a leading cause of maternal and fetal morbidity and mortality worldwide. Exciting discoveries in the last decade have contributed to a better understanding of the molecular basis of this disease. Epidemiological, experimental, and therapeutic studies from several laboratories have provided compelling evidence that an antiangiogenic state owing to alterations in circulating angiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
95
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(113 citation statements)
references
References 180 publications
3
95
0
2
Order By: Relevance
“…This devastating pregnancy complication affects 5-8 % of all pregnancies worldwide and is characterized by de novo onset of hypertension and proteinuria in pregnant women [1][2][3][4][5][6][7][8][9][10]. The new clinical definition also includes severe hypertension and end-organ dysfunction which may or may not occur in conjunction with proteinuria after 20 weeks of gestation [2].…”
Section: Introductionmentioning
confidence: 97%
“…This devastating pregnancy complication affects 5-8 % of all pregnancies worldwide and is characterized by de novo onset of hypertension and proteinuria in pregnant women [1][2][3][4][5][6][7][8][9][10]. The new clinical definition also includes severe hypertension and end-organ dysfunction which may or may not occur in conjunction with proteinuria after 20 weeks of gestation [2].…”
Section: Introductionmentioning
confidence: 97%
“…18 Adenosine is a key signaling molecule that orchestrates the cellular response to hypoxia, energy depletion, and tissue damage by the activation of G-protein-coupled cell surface receptors. Recently, we demonstrated that placental adenosine is elevated in patients with preeclampsia.…”
Section: Hypertensionmentioning
confidence: 99%
“…There have been many studies on the etiology of preeclampsia (Lwaleed et al, 2011); however, the pathogenesis of pre-eclampsia remains unclear. Many factors play important roles in the development of pre-eclampsia, such as preexisting hypertension, diabetes, high body mass index and obesity (Das, 2015;Hod et al, 2015;Mol et al, 2016). Pre-eclampsia in 35% of pregnant women is reportedly resulted from genetic factors (Hod et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Many factors play important roles in the development of pre-eclampsia, such as preexisting hypertension, diabetes, high body mass index and obesity (Das, 2015;Hod et al, 2015;Mol et al, 2016). Pre-eclampsia in 35% of pregnant women is reportedly resulted from genetic factors (Hod et al, 2015). Many genetic factors influence the pathogenesis of pre-eclampsia, such as glutathione S-transferase pi 1, glutathione peroxidase 1, matrix metalloproteinase-9, interleukin-8, tumor necrosis factor-a, interleukin-1-b, insulin receptor genes (Gao et al, 2016;Sun et al, 2016a,b;Tavakkol Afshari et al, 2016;Andraweera et al, 2017).…”
Section: Introductionmentioning
confidence: 99%